1997
DOI: 10.1074/jbc.272.35.22259
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of the Cyclin A Promoter by Transforming Growth Factor-β1 Is Associated with a Reduction in Phosphorylated Activating Transcription Factor-1 and Cyclic AMP-responsive Element-binding Protein

Abstract: Transforming growth factor (TGF)-␤1 prevents cell cycle progression by inhibiting several regulators, including cyclin A. To study the mechanisms by which TGF-␤1 down-regulates cyclin A gene expression, we transfected reporter plasmids driven by the cyclin A promoter into mink lung epithelial cells in the absence and presence of TGF-␤1. The TGF-␤1-induced down-regulation of cyclin A promoter activity appeared to be mediated via the activating transcription factor (ATF) site, because mutation of this site aboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 48 publications
0
34
1
Order By: Relevance
“…Similarly, Djaborkhel et al reported that in lymphoma cells, TGF␤ impedes CREB1 and ATF2 from binding to the CRE site of the cyclin A promoter (9). However, in mink lung epithelial cells (Mv1Lu), the CREB-CRE interaction was found to be unaffected by TGF␤ (37). Although the exact cause of this discrepancy is unknown, one apparent difference between the present study and the one by Yoshizumi et al is the duration of TGF␤ treatment.…”
Section: Vol 27 2007 Creb-dependent Regulation Of Cyclin a 3495contrasting
confidence: 55%
“…Similarly, Djaborkhel et al reported that in lymphoma cells, TGF␤ impedes CREB1 and ATF2 from binding to the CRE site of the cyclin A promoter (9). However, in mink lung epithelial cells (Mv1Lu), the CREB-CRE interaction was found to be unaffected by TGF␤ (37). Although the exact cause of this discrepancy is unknown, one apparent difference between the present study and the one by Yoshizumi et al is the duration of TGF␤ treatment.…”
Section: Vol 27 2007 Creb-dependent Regulation Of Cyclin a 3495contrasting
confidence: 55%
“…In support of this assumption PP2A was reported to remove phosphate from serine-133 of CREB in HepG2 cells (40), and transforming growth factor ␤ was found to downregulate cyclin A by causing dephosphorylation of CRE binding proteins, a reaction which is counterbalanced by SV40 ST protein (42). On the other hand, peptide inhibitors of protein phosphatase 1 were found to increase phosphorylation of CREB in NIH 3T3 fibroblasts; in this study, SV40 ST antigen was found to have no effect on the phosphorylation status of CREB (2).…”
Section: Discussionmentioning
confidence: 71%
“…For instance, at many promoters the YY1 protein activates transcriptional initiation by stimulating recruitment of RNA polymerase II while at other promoters YY1 represses transcription by sequestering CREB/ATF (95). Similarly, depending on context, the cyclin A gene has also been shown to be either up-or down-regulated through its upstream CREB/ATF site (15,16,92,93).…”
Section: Discussionmentioning
confidence: 99%